ANALYSIS OF FACTORS THAT AFFECT DIFFICULTIES IN LEARNING MATHEMATICS DURING THE PANDEMIC - Souhoka, Ivone Adriana (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
Covid-19 is a virus that originated in Wuhan Chaina in 2019. The spread of this virus has spread to 234 countries including Indonesia. The government took the decision to implement health protocols, PPKM and vaccination. Due to the Covid-19 virus, there are impacts in various sectors, one of which is the education sector. In the field of online learning education, due to the decision taken by the government, namely PPKM, over time with a decrease in cases, the government began to reactivate limited school activities and January 2022 entered the new normal phase. In these three phases, there are obstacles in the education sector. This study aims to determine whether or not ordinal regression is feasible to use and determine whether school environmental factors, learning motivation and study habits affect mathematics learning difficulties during a pandemic and how much the independent variable can affect the dependent variable. Research with the distribution of questionnaires at SMK Bina Bangsa. The independent variables are school environment, learning motivation and study habits and dependent variables of difficulty learning mathematics during the pandemic. Ordinal logistic regression model with logit(Y1) equation = θ1+β1 X1+β2 X2+. +βp Xp. Goodness of fit test to find out whether the regression model is feasible, simultaneous parameter test comparing models without predictor variables, wald test knowing the influential variable and Nagelkerke test results for the magnitude of influence. The results showed ordinal regression on the independent variable to the dependent variable by 45%.